COVID-19 DAN PENUNDAAN KEPULANGAN MIGRAN PELAJAR INDONESIA DI LUAR NEGERI - Inayah Hidayati (Research Centre for Population, Indonesian Institute of Sciences, 2020)
The COVID-19 pandemic is the reason some Indonesian student migrants to delaying their return-home. Various factors that inhibit return migration such as health, security, transportation and local immigration rules make student migrants stay abroad. Objective: This research aims to understand the migration decision-making process of Indonesian student migrants abroad on postponed their return-home to Indonesia on May-December 2020. Methods: The data collected included quantitative from a survey and qualitative data from interviews. Result: The decision-making process for migrant students arises from themselves and strengthened by the family and community, including information from their social networks. The impact of some student migrants who delay their return is the economic situation, especially for students who rely on their scholarships. To relieve the burden on student migrant, the Indonesian government can provide daily need aid. The Indonesian government also need diplomate to educational institutions to reduce their tuition fees and extend residence permit.